Novel N-TiO2/SiO2/Fe3O4 nanocomposite as a photosensitizer with magnetism and visible light responsiveness for photodynamic inactivation of HeLa cells in vitro. Issue 10 (July 2019) - Chang, Tong; Hou, Yajun; Wang, Fengze; Wang, Yumei; Bi, Yushui
Abstract: Semiconductor photocatalyst materials based on TiO2 are potential photosensitizers for photodynamic therapy of cancer. Despite its effectiveness under ultraviolet light, pure TiO2 shows almost no photocatalytic activity under visible light because of its wide intrinsic band gap energy (anatase, 3.2 eV). Besides, TiO2 has no magnetic delivery property. In this study, an inorganic nanocomposite, N-TiO2 /SiO2 /Fe3 O4, is successfully prepared in three steps by means of co-precipitation, Stöber and sol-gel methods. Deep characterization results by XRD, TEM, XPS, UV–vis DRS, FL and magnetic hysteresis loop reveal that N-TiO2 /SiO2 /Fe3 O4 has core-shell structure, magnetic property and visible-light-response capability. As a potential photosensitizer for photodynamic therapy, it shows a stronger photodynamic suppression effect on proliferation of HeLa cells than TiO2 under the irradiation of xenon light.